Artifacts of Empathy: Cultivating, Identifying, and Assessing Students’ Development and Written Articulations of Empathy in a Community Engagement Course - Stephanie May de Montigny (Teaching & Learning Inquiry: The ISSOTL Journal)
This research recounts a scholarship of teaching and learning (SoTL) project aimed at facilitating students’ empathic development while also offering ways to identify and assess students’ written expressions of empathy. I ground this work in an exploration of the many processes labelled as empathy and the reasons for including empathy as a course learning outcome. While participating in the Lighted School House program, I explored using progressive, or stacked, writing reflections to help students build, recognize, and articulate their own empathy. I conducted a close reading of final reflection papers in two offerings of a second-year community engagement course (in 2017 and 2019) in which students worked with an afterschool program in local elementary and middle schools. This enabled me to identify features of student writing—the evidence or “artifacts”— that illustrated their understanding of empathy, others’ perspectives, and positionality. To assess the depth and complexity with which students articulated their empathy, I devised a scale to identify these written expressions as novice, intermediate, or advanced. The analysis showed the importance of using an “imagine-other” perspective rather than merely imagining oneself in another’s situation, valuing others to inspire empathic action, and using conversation as a powerful tool for developing empathy. The project points to pedagogical practices that encourage students to employ effective conversation and listening skills in community engagement. This research suggests ways to help students better express their empathy by revising prompts and rubrics to clarify the particular empathic processes targeted and to foster strong writing skills.